Leaders who lead successfully : guidelines for organizing to achieve innovation - Lamberg, Teruni D. (Rowman & Littlefield Publishers, 2018)
"This book will help readers develop their leadership skills by drawing from a higher purpose to find passion to lead purposefully and creatively. Team leaders will learn how to identify a problem from a 360-degree perspective to meet the needs of the customer and how to select a diverse team that can work synergistically together to innovate. This process involves matching expertise to project and project to expertise. Successful leaders acquire a combination of knowledge and experiences help them make better decisions. Dr. Lamberg also provides strategies for growing as a leader and for making decisions so that project goals and team members' expertise align to create optimal conditions for thinking and productivity."--Publisher's description